FRI0213 Identification of Synovitis in Patients with Rheumatoid Arthritis in Clinical Remission during Therapy with Tocilizumab. (15th July 2016) - Panasyuk, E.; Smirnov, A.; Fedorenko, E.; Gavva, T.; Gubar, E.; Loginova, E.; Lukina, G.; Luchikhina, E.; Tsvetkova, E.; Avdeeva, A.; Alexandrova, E.; Nasonov, E.
Abstract : Background: The aim of therapy rheumatoid arthritis (RA) is the achievement of remission of the disease and slowing destruction of the joints. Tocilizumab (TCZ), anti-interleukin-6 receptor monoclonal antibody was used in treatment of active RA. TCZ has a rapid positive effect on the clinical manifestations and laboratory disoders, slowing destruction of joints in RA. Objectives: To assess the effect of TCZ on synovitis on MRI of bilateral wrist and metacarpophalangeal joints in accordance with the OMERACT RA MRI scoring system (RAMRIS). Methods: 43 adult patients with active RA were enrolled in the open label, phase IV trial to confirm the effectiveness and safety TCZ. Average age (median, interquartile range) 50, 5 (43, 0–55, 0) years, duration of RA 56, 5 (23, 0–81, 0) months, RF (+) 81%, ACCP (+) 77%. Patient had to be naive to biologics and have moderate to severe active RA (based on the 1987 ACR criteria). Patients remained on stable doses of disease-modifying antirheumatic drugs and received TCZ 8 mg/kg every 4 weeks for 24 weeks (total 6 infusions). Disease remission was assessed according to the criteria of EULAR and EULAR/ACR 2011. MRI performed at 0 and 24 weeks of observation. Results: Before therapy indices DAS28 (6, 4; 5, 9–7, 0), CDAI (41, 5; 32, 0–53, 0) and SDAI (45, 0; 36, 2–57, 0) corresponded to high activity of RA. The value of DAS28 to 24 weeks of treatment was 2, 1; 1, 3–2, 8, p<0.05. Indicators SDAI and CDAI up to 24th week match the low activity of RA (4, 4; 2, 0–8, 8 and 3, 6; 1, 4–7, 6, respectively). Remission was achieved by 24 weeks of treatment on indices: DAS28<2.6 for 30 patients (71%), CDAI<2.8 to 14 (33%), SDAI<3.3 to 13 (31%) and according to the criteria of ACR/EULAR 2011 (Boolean) – 10 (24%). MRI of the bilateral wrist and metacarpophalangeal joints was performed for patients who achieved remission according to the DAS28 criteria (n=27) and Boolean (n=10). Synovitis was detected in 81.5% and 80%, osteitis in 11.1% and 10% of patients, respectively. Conclusions: Despite the pronounced clinical effect of TCZ in patients with RA and remission according to the criteria of DAS28 and ACR/EULAR, synovitis was detected in most patients. MRI examination allows to observe the patients during the therapy to achieve complete remission of the disease. Disclosure of Interest: None declared